O teor testemunhal da poesia de guerra de Carlos Drummond de Andrade - Rezende, Rosana Gondim (2021)
Known as the era of the machine, of electric light, of speed, the 20th century was marked by great inventions, giving man the feeling of power. In art, the Cultural Revolution of Modernism, seeking assimilation and synchronization with European vanguards, dissolved borders. However, it is practically impossible to allude to that time without also mentioning the horrors of wars, whether they are narrated in testimonies from those who were involved in the conflicts, whether they are translated by the testimonies of those who accompanied them on the radio, letters or telegrams. In this sense, artistic manifestations, in particular, become channels through which the impacts and traumas caused by those are expressed. Therefore, the facts that marked the Second World War are reflected in the works of many modernist and contemporary writers. Among them, the poet Carlos Drummond de Andrade calls our special attention. Our purpose, therefore, is to analyze five poems by this writer, contained in A Rosa do Povo, and examine the poetic images that translate the impressions and feelings of a poet who did not witness the war, showing the tension between presence and representation. Thus, through the recognition of the thematic and stylistic particularities of this poet, in his poems that deal with World War II, above all by the analysis of the poems “News”, “Moscow Telegram”, “Letter to Stalingrado”, “Vision 1944” and “With the russian in Berlin”, contained in A Rosa do Povo, we intend to verify how Drummond's poetry approaches the European reality of war; what are the images of a poet who did not witness the war; how poetry contemplates the poet's desire to share the suffering of those who have experienced war. These issues can be supported by the theme of poets who witnessed the war, such as Paul Celan, and his poems on that subject, more specifically "Escape from death". We will also identify the different perceptions of the poets and the recurring thematic elements in their poetry, which mark the relationship between literature and war, considering the references of presence and representation. For this purpose, we selected, mainly, as a theoretical reference, the scholars Walter Benjamin, Theodor W. Adorno, Eric Hobsbawm, Northrop Frye, Anthony Giddens, Tiphaine Samoyault, Alfredo Bosi, Antonio Cândido, Ivan Junqueira, José Guilherme Merquior, Murilo Marcondes de Moura , Iumna Maria Simon, Jaime Ginzburg, Afonso Romano de Sant'Anna, Betina Bischoff, Vagner Camilo, Márcio Seligmann-Silva, Claudio Guillén, Sandra Nitrini, Flávio Kothe and Modesto Carone.